Subject and generic skills in unity - Information literacy in collaboration for enhanced learning - Grandsjö, Linda; Zettergren, Ann-Sofie (Nordic Journal of Information Literacy in Higher Education, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> <![endif]–> Our aim is to highlight and exemplify the value of collaboration across professional borders concerning information literacy and academic writing. We believe that by supporting our students in their development of information literacy, we also contribute to a deeper subject learning. There is no conflict between the two, an integration of IL benefits both areas and above all, the students' learning. Collaboration between faculty teachers and liaison librarians enable a learning environment that can take advantage of the interaction between the use of generic skills and subject skills. There is also the importance of constructive alignment within in the syllabus, which the Social Science Faculty at Lund University has been working on since the Bologna Process. When learning outcomes on information literacy where added to the syllabi at courses at the faculty in autumn 2007, a platform for collaboration between teachers and librarians was staged. In this presentation we would like to highlight two examples of information literacy sessions for students, both developed in cooperation with teachers and both designed to meet a special need in the course at present. Example 1 On a second term course in political science the teacher noticed problems with the quality of the assignments handed in concerning the use of scholarly articles. Through collaboration and dialogue the IL class was integrated as a natural part within the subject course. A cross-fertilization came to be in working integrated with the assignment in IL class, through searching and critically evaluating sources subject learning was also boosted and the other way around. The assignments improved and motivation was raised. Example 2 First term students at a course in sociology were to write a paper as a part of their examination. The main problem for several students was addressed as plagiarism including several variables: lack of knowledge, progression and information. The aim was to demystify academic writing and make it as transparent as possible. The solution was to take off in the texts and the writing process together with the students, and to use the different competences from teacher and librarian. Through cross professional collaboration, multiple aspects of academic writing originating from the diverse competences were clarified and addressed the topic from different angles. Results of collaboration The quality of the assignments increased The questions asked by the students where more focused and better addressed Increased motivation to attend IL class with subject relevant context and clear connection to the examination (constructive alignment) Deepened subject learning within the active search process The information literacy sessions as an integrated part of the ordinary schedule Decoding of the academic thought-search-writing process <!–[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>